Business Process Improvement at Rosokku - Wahyuni, Eka Dyar; Sugiarto (Future Science, 2020)
Rosokku is a technology-based startup that collects and processes waste (paper-based). Rosokku takes paper-based waste based on customer requests. And for this pick-up, there has been an agreement with the customer about the day of the pick-up beforehand. The convenience of this process (people throw away their paper waste and at the same time they get money) has started to rise in demand from the community, especially among college students. Up to this day, Rosokku has used media such as WhatsApp and Instagram to engage with its clients so far. As the number of clients has risen, in deciding the pick-up schedule, rosokku has begun to become overwhelmed. There is a lot of data that is not well documented. The team began to have difficulty tracking their financial transactions as well. Therefore, this research aims to solve these problems by reviewing existing business processes and developing new business processes to improve current business processes (conduct gap analysis). The results of this research are new business processes that will be implemented later on to the application (functional requirement).